The influence of mutually beneficial and self-beneficial situations on the lying behavior and cognition of Chinese 4- to 5-year-old children - Kang, Dan; Zhang, Yingjie; Xu, Xiwu; Li, Jiajia (Frontiers in Psychology, 2025)
BackgroundChildren’s moral development is influenced by their sociocultural context. However, relatively few studies have investigated whether the sociocultural context affects children’s lying behavior and cognition and the relation between them.MethodsThe present study was designed to examine this question in two experiments by posing two moral dilemmas: lying is good for mutually beneficial (honesty conflicts with mutual interests) and lying is good for self-beneficial (honesty conflicts with self-interests). Experiment 1 used the “hide-and-seek” game to investigate the lying behavior of 96 Chinese 4- to 5-year-old children. Experiment 2 used two videos to investigate lying cognition (conceptualization of lying, moral assessment of lying, and prediction of lying) with the same group of children.ResultsIn Experiment 1, children lied more in mutually beneficial situations than in self-beneficial situations. Experiment 2 revealed that, compared with self-beneficial situations, children in mutually beneficial situations were more likely to judge untrue statements as truth, to evaluate lying positively, and to predict that they would lie. Further, in mutually beneficial situations, children’s predicted and actual lying behaviors are significantly positively correlated.ConclusionThese findings support the folk model and highlight the influence of sociocultural factors on lying in Chinese 4- to 5-year-old children. They offer meaningful insights into the development of early moral understanding and behavior.